First case of Francisella bacteraemia in Western Australia. (November 2015) - Aravena-Román, Max; Merritt, Adam; Inglis, Timothy J.J.
Abstract: Francisella species are Gram-negative, nonmotile, pleomorphic coccobacilli, facultative intracellular fastidious bacteria. We report the isolation of a Francisella- like species from a blood culture collected from a 44-year-old bacteraemic patient in Perth, Western Australia. The organism was identified to species level by 16S rRNA sequencing and by fatty acid methyl esters analysis. The strain genotypically resembled Francisella hispaniensis, a species previously isolated from human blood in Spain.